IC 9413 The Availability Of Titanium In Market Economy Countries - A Minerals Availability Appraisal - Jennifer A. Slatnick (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The U.S. Bureau of Mines estimated the potential availability of titanium from 39 mines and deposits in 12 market economy countries. The evaluated properties account for 76 pet of the market economy country demonstrated resources, which total 603 Mt of contained titanium dioxide (Ti02) in the minerals rutile, ilmenite, leucoxene, and anatase, and represent 95 pct of current production. Approximately 250 Mt of contained Ti02 could be economically recovered from evaluated titanium operations at January 1992 market prices. In terms of mineral concentrates, this equals approximately 19 Mt of rutile concentrate, 110 Mt of ilmenite concentrate, 47 Mt of synthetic rutile concentrate (in addition to the ilmenite), and 160 Mt of titanium slag that could be recovered. Over the past decade, the titanium minerals industry has adapted to the changing market. In the 1980's, titanium producers expanded production because of the rising demand for titanium products. Today, the titanium industry is in a state of overcapacity, and byproduct revenues, such as that from zircon, have become essential in keeping operations profitable. The industry has also witnessed a greater dependence on upgraded ilmenite products, such as titanium slag and synthetic rutile, because of the expense of rutile and the lower wastes emitted from these upgraded products. As a result of this dependence on upgraded ilmenite products, South Africa has become a leading titanium producing country and has displaced Australian production.